Analysis of Moral Crisis in Elementary School in the Millennial Era - Fajar Budiyono; Syaiful Bahri; Sama' Sama' (Edumaspul: Jurnal Pendidikan, 2022)
The moral crisis is the fading of attitudes, character and behavior that are sustainable with the goodness of each individual. The moral crisis that occurred among elementary school students, for example, was the loss of the culture of saying the words "sorry, please, excuse me and thank you". This is a basic thing in ethics, and now this basic thing in ethics has faded and is almost never heard of again. This happens because elementary school students do not do enough literacy and filter foreign cultures that enter Indonesia. This paper applies a qualitative descriptive method with a type of research in the form of library research, namely collecting information or scientific papers that have a relationship with literary literature reviews. The main purpose of this research is for the reader to understand what happened regarding the moral crisis in the millennial era at the elementary school level in comprehensive scientific research. By conducting character education for elementary school students and helping them to improve their morals, the moral crisis that is currently being faced can be corrected little by little and the positive impact will greatly affect the future of young people.